Kekayaan Intelektual Dalam Ekonomi Islam - Mesrawati Mesrawati; M Yasir Nasution; Sugianto Sugianto (Forum Kerjasama Pendidikan Tinggi, 2023)
Intellectual property rights are material rights, namely rights to an object originating from the work of the brain or the work of reasoning ratios. With regard to IPR, the Indonesian cultural climate has offered something different from Western legal culture. Creators or inventors in Indonesia are very pleased when their creations are reproduced or announced by others. Judging from the fundamental aspect of copyright, Islamic Economics first recognizes property rights. intellectual property rights have met the requirements as assets and property rights in the perspective of Islamic economics, both in terms of their characteristics and in terms of how they are acquired and transferred. This is based on the opinion of the majority of scholars which are commonly used in modern legal systems among Muslims, as well as in accordance with the general customs of society. So that other people can use it for the benefit of scientific development as well as for economic or business interests by adhering to existing regulations. The property rights in question are not property rights like the capitalist economy which is based on individual property rights or the socialist economy which is based on the philosophy of collectivism.